Strategic Analysis of Terna Energy - Avlonitis, Alkinoos; Kupec, Václav; Písař, Přemysl, 1978-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
We are living in turbulent times with unprecedented opportunities and challenges that lie ahead of us. This is especially true in the energy sector, as it is undergoing a major transition from ordinary methods to renewable sources. The aim of the thesis is to carry out a comprehensive analysis of the external and internal environment of the selected company and provide suggestions for the company’s future development. This is based on the literature review where tools currently used are reviewed and implemented. The key findings are that there is a lot of pressure from governments to implement new technologies. Additionally, there are high levels of competition between in that industry with extremely limited ways of differentiation. One of the recommendations given is to fund research surrounding energy storage as that was deemed one of the main issues. Another recommendation is to address some of the potential issues of the technology used in order to be perceived as transparent and honest. With the correct implementation of these recommendations the organization will improve and grow further.
Vedoucí práce: Václav Kupec
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses